دلالة المكان في مسرحية " الطاغية " لمحمد غمري - معمـري, فواز (قــــــراءات, 2019)
يسعى هذا المقال إلى الكشف عن ما يحمله المكان من دلالات وعلامات أيقونية يمكنها المساهمة في عملية التواصل بين القارئ والنص، وكذا إيضاح الأهمية والدور الذي يلعبه المكان في سير الأحداث باعتباره مجالاً وحيزاً تتفاعل وتتحرك فيه الشخصيات. وقد كانت خطوات البحث كتالي: في البداية نحاول تقديم مفهوم للمكان لغة واصطلاحا، ثم دراسة الأمكنة الدالة في مسرحية "الطاغية"، مع توضيح العلاقة التي تربط تلك الأمكنة بالشخصيات، كالقصر، وغرفة العرش، والشارع والملعب، وتنوعها بين أمكنة للألفة وأخرى معادية، لنخلص في الأخير إلى الدور الذي يؤديه المكان في تطوير الأحداث والتأثير في الشخصيات.   Abstract: This article seeks to reveal what holds " place" of semantics meaning and iconic signs, they can contribute to the process of communication between the reader and the text, as well as clarify the importance and the role of place in the course of events as an area and space where characters interact and move. Research steps were as follows: In the beginning we are trying to introduce the concept of the place the language and idiomatically, then studying places keywords in the play "The tyrant", indicating the relationship between those places with characters, as: the palace, the throne room, the street, the stadium, and their diversity between places of familiarity and others of enemy, to conclude in the last to the role of place in the development of events and effect on characters.